CD24, CD44 and EpCAM enrich for tumour-initiating cells in a newly established patient-derived xenograft of nasopharyngeal carcinoma - Hoe, S.L.L.; Tan, L.P.; Abdul Aziz, N.; Liew, K.; Teow, S.Y.; Abdul Razak, F.R.; Chin, Y.M.; Mohamed Shahrehan, N.A.; Chu, T.L.; Mohd Kornain, N.K.; Peh, S.C.; Koay, C.E.; et al. (Nature Publishing Group, 2017)
Subpopulations of nasopharyngeal carcinoma (NPC) contain cells with differential tumourigenic properties. Our study evaluates the tumourigenic potential of CD24, CD44, EpCAM and combination of EpCAM/CD44 cells in NPC. CD44br and EpCAMbr cells enriched for higher S-phase cell content, faster-growing tumourigenic cells leading to tumours with larger volume and higher mitotic figures. Although CD44br and EpCAMbr cells significantly enriched for tumour-initiating cells (TICs), all cells could retain self-renewal property for at least four generations. Compared to CD44 marker alone, EpCAM/CD44dbr marker did not enhance for cells with faster-growing ability or higher TIC frequency. Cells expressing high CD44 or EpCAM had lower KLF4 and p21 in NPC subpopulations. KLF4-overexpressed EpCAMbr cells had slower growth while Kenpaullone inhibition of KLF4 transcription increased in vitro cell proliferation. Compared to non-NPC, NPC specimens had increased expression of EPCAM, of which tumours from advanced stage of NPC had higher expression. Together, our study provides evidence that EpCAM is a potentially important marker in NPC.